Kualitas Pelayanan PT. Pos Indonesia (Persero) Cabang Sukamerindu, Kota Bengkulu - Yasmin Meri Susianti; Kahar Hakim; Alimansyah, Alimansyah (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
The purpose of this study is to examine the service quality of PT. Pos Indonesia (Persero), Sukamerindu Branch, Bengkulu City. The method used is descriptive and qualitative, with data collection techniques including observation, interviews, and documentation. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. The study assessed several dimensions: tangible evidence, reliability, responsiveness, assurance, empathy, and good corporate governance (GCG), particularly focusing on PT. Pos Indonesia’s ethical adaptation to the local cultural values and its active role in supporting the community’s economic development as part of its corporate social responsibility. The findings indicate that the service quality at the post office is poor. Based on these results, the researcher recommends that the central management of PT. Pos Indonesia (Persero) implement strict regulations regarding excellent service standards for all employees across Indonesia. In addition, the company should provide suggestion boxes and a call center with an accessible telephone number for customers to report poor service. The public is also encouraged to play a more active role in monitoring the performance of this state-owned enterprise (SOE) by submitting complaints to the Ombudsman or through the government reporting platform, lapor.go.id.